Effects of early-life adversity on white matter diffusivity changes in patients at risk for major depression - Frodl, Thomas (Canadian Medical Association, 2012)
BACKGROUND: Relatives of patients with major depressive disorder (MDD) and people who experienced early-life adversity are at risk for MDD. The aim of our study was to investigate whether unaffected first-degree healthy relatives (UHRs) of patients with MDD show changes in white matter fibre connections compared with healthy controls and whether there are interactions between early-life adversity and these microstructural changes. METHODS: Unaffected, healthy first-degree relatives of patients with MDD and healthy controls without any family history for a psychiatric disease underwent high angular resolution diffusion imaging with 61 diffusion directions. Data were analyzed with tract-based spatial statistics, and findings were confirmed with tractography. RESULTS: Twenty-one UHRs and 24 controls participated in our study. The UHRs showed greater fractional anisotropy than controls in the body and splenium of the corpus callosum, inferior fronto-occipital fasciculus (IFO), left superior longitudinal fasciculus (SLF) and right fornix. The UHRs who experienced more early-life adversity had greater fractional anisotropy than those with less early-life adversity in the splenium of the corpus callosum, fornix, IFO and SLF; in controls, early-life adversity was found to be associated with decreased fractional anisotropy in these fibre tracts. LIMITATIONS: Studying participants’ strategies for coping with early-life adversity would have been helpful. Crossing fibres in tracts are a general limitation of the method used. CONCLUSION: Altogether, our findings provide evidence for greater fractional anisotropy in UHRs and for interaction between early-life adversity and family risk on white matter tracts involved in cognitive–emotional processes. Whether stronger neural fibre connections are associated with more resilience against depression needs to be addressed in future studies.